Ain't no mountain high enough: plant invasions reaching new elevations. Issue 9 (31st October 2009) - Pauchard, Aníbal; Kueffer, Christoph; Dietz, Hansjörg; Daehler, Curtis C; Alexander, Jake; Edwards, Peter J; Arévalo, José Ramón; Cavieres, Lohengrin A; Guisan, Antoine; Haider, Sylvia; Jakobs, Gabi; McDougall, Keith; et al.
Abstract : Most studies of invasive species have been in highly modified, lowland environments, with comparatively little attention directed to less disturbed, high‐elevation environments. However, increasing evidence indicates that plant invasions do occur in these environments, which often have high conservation value and provide important ecosystem services. Over a thousand non‐native species have become established in natural areas at high elevations worldwide, and although many of these are not invasive, some may pose a considerable threat to native mountain ecosystems. Here, we discuss four main drivers that shape plant invasions into high‐elevation habitats: (1) the (pre‐)adaptation of non‐native species to abiotic conditions, (2) natural and anthropogenic disturbances, (3) biotic resistance of the established communities, and (4) propagule pressure. We propose a comprehensive research agenda for tackling the problem of plant invasions into mountain ecosystems, including documentation of mountain invasion patterns at multiple scales, experimental studies, and an assessment of the impacts of non‐native species in these systems. The threat posed to high‐elevation biodiversity by invasive plant species is likely to increase because of globalization and climate change. However, the higher mountains harbor ecosystems where invasion by non‐native species has scarcely begun, and where science and management have the opportunity to respond in time.